(Re) configurações do eu: a produção de autorretratos fotográficos como ficção/encenação - Perez, Karine Gomes (2010)
This theoretical and practical research proposes to investigate the artistic creation process of photographic self-portraits. It analyzes the possibilities of identity reconfigurations, involved in this process, resulting in the series (Re)Configurações do eu [(Re)Configurations of me], produced from two different types of images: photos 3x4 of documents and fictional and dramatized photographs in domestic environment. The series is composed of works created from these contaminated photographs by pictorial means (encaustic painting) and digital manipulations (overlaps and juxtapositions of images in digital laboratory), printed on matte canvas. The works present the hidden body with other people's clothing and veils, establishing direct relationship with the camera that registers their "poses/actions". They also present space-temporal compositions overlapped, contained in each layer of the images. Through these procedures, the self-portrait s subgenre and the subjects identity are problematized, showing not an artist's identity seen as "mesmidade" but (re)configurations of me through hidings and possibilities of multiplications identity, produced in the images. Like this, from the documents photographs, that indicate a standardized "me", the work reach the production of many dramatized mes who are creations or fictions.